2003
DOI: 10.1007/s00204-003-0458-7
|View full text |Cite
|
Sign up to set email alerts
|

Markers of experimental acute inflammation in the Wistar Han rat with particular reference to haptoglobin and C-reactive protein

Abstract: C-reactive protein (CRP), haptoglobin (Hp) and fibrinogen (Fbgn) are acute phase reactants (APRs), the blood levels of which increase during acute inflammation. However, although the levels of these APRs are used to monitor inflammation in man, their usefulness and sensitivity as markers of inflammation in rodents are less clear. We therefore wished to evaluate, in a comparative fashion, a prototype immunoassay for serum CRP, a commercial assay for serum Hp, and an automated assay for Fbgn, using a model of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 25 publications
9
83
1
Order By: Relevance
“…As another inflammatory marker, we measured haptoglobin, rather than CRP, because CRP is not an ideal measurement of the liver's response to inflammatory status in rats (34). Plasma haptoglobin levels were significantly less in E than in S rats by 4 wk of intervention and remained below levels in S rats throughout the rest of the study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As another inflammatory marker, we measured haptoglobin, rather than CRP, because CRP is not an ideal measurement of the liver's response to inflammatory status in rats (34). Plasma haptoglobin levels were significantly less in E than in S rats by 4 wk of intervention and remained below levels in S rats throughout the rest of the study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Haptoglobin peaked at 2 wk. In rats, a faster response has been reported for Hp, achieving maximum values 24 hr after an inflammatory stimulus (Deak et al, 1997;Kataranovski et al, 1999;Giffen et al, 2003;Matić et al, 2004). Nevertheless, the magnitude of the increase observed in Hp was similar to other studies in rats (Matić et al, 2004).…”
Section: Response After Turpentine Administrationmentioning
confidence: 97%
“…Some studies indicate that cytokines, such as TNF-α, induced rat liver cell cytotoxicity, and the AST level increased at the 12 th hour and reaching its maximum level at the 36 th hour [31,33]. In our study, AST levels were used as the indicator of liver toxicity and organ failure.…”
Section: Ast=aspartat Amino Transpherase Crp= C-reactive Protein Ilmentioning
confidence: 82%
“…In some trials, it has been demonstrated that CRP levels rise in a statistically significant manner and are an indicator of inflammation [30,31]. Kuster et al [32] have reported that, while the diagnostic sensitivity of CRP before the clinical appearance of peritonitis is 18%, its sensitivity is 93% at the time of the clinical diagnosis.…”
Section: Ast=aspartat Amino Transpherase Crp= C-reactive Protein Ilmentioning
confidence: 99%